QUALITY MANAGEMENT IN ENGINEERING a scientific and systematic approach. - Lim, Jong Seong ([S.l.] : CRC PRESS, 2019)
This book introduces fundamental, advanced, and future-oriented scientific quality management methods for the engineering and manufacturing industries. It presents new knowledge and experiences in the manufacturing industry with real world case studies. It introduces Quality 4.0 with Industry 4.0, including quality engineering tools for software quality and offers lean quality management methods for lean manufacturing. It also bridges the gap between quality management and quality engineering, and offers a scientific methodology for problem solving and prevention. The methods, techniques, templates, and processes introduced in this book can be utilized in various areas in industry, from product engineering to manufacturing and shop floor management. This book will be of interest to manufacturing industry leaders and managers, who do not require in-depth engineering knowledge. It will also be helpful to engineers in design and suppliers in management and manufacturing, all who have daily concerns with project and quality management. Students in business and engineering programs may also find this book useful as they prepare for careers in the engineering and manufacturing industries. Presents new knowledge and experiences in the manufacturing industry with real world case studies Introduces quality engineering methods for software development Introduces Quality 4.0 with Industry 4.0 Offers lean quality management methods for lean manufacturing Bridges the gap between quality management methods and quality engineering Provides scientific methodology for product planning, problem solving and prevention management Includes forms, templates, and tools that can be used conveniently in the field
OCLC-licensed vendor bibliographic record.
Keywords: TECHNOLOGY / Engineering / Industrial; TECHNOLOGY / Manufacturing; TECHNOLOGY / Quality Control; Quality control